2011
DOI: 10.1038/aps.2011.83
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological mechanisms underlying the antinociceptive and tolerance effects of the 6,14-bridged oripavine compound 030418

Abstract: Aim: To investigate possible pharmacological mechanisms underlying the antinociceptive effect of and tolerance to N-methyl-7α-[(R)-1-hydroxy-1-methyl-3-(thien-3-yl)-propyl]-6,14-endo-ethanotetrahydronororipavine (030418), a derivative of thienorphine. Methods: The binding affinity and efficacy of 030418 were determined using receptor binding and guanosine 5′-O-(3-[ 35 S]thio)triphosphate ([ 35 S]GTPγS) assays in CHO-μ, CHO-κ, CHO-δ, and CHO-ORL1 cell membranes. The analgesic activity of and tolerance to 030418… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Here, we employed a training cluster of five fentanyls (fentanyl, 3‐methylfentanyl, sufentanil, remifentanil, and carfentanil) and six morphines (morphine, codeine, heroin, 6‐monoacetylmorphine, thienorphine, and 030418 ) to test the classification possibility. Direct classification between two classes was obviously achievable.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we employed a training cluster of five fentanyls (fentanyl, 3‐methylfentanyl, sufentanil, remifentanil, and carfentanil) and six morphines (morphine, codeine, heroin, 6‐monoacetylmorphine, thienorphine, and 030418 ) to test the classification possibility. Direct classification between two classes was obviously achievable.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, some orvinols, including etorphine, buprenorphine, thienorphine, the BU08028 and BU08070 series, the BU08073 series, BU10038 and the OREX-1019 series, as well as the phenyl substituted analogs of buprenorphine, exhibited low affinity and/or potency to the nociceptin/orphanin FQ opioid peptide (NOP) receptor, and functional regulation of NOP receptor was involved in analgesia, locomotor activity, abuse liability and reward, as well as other behavioral changes. , Whether the unique profile of SLL-627 was correlated to its potential action toward the NOP was not investigated in this work. Due to high variability and heterogeneity of data currently available, it is also difficult to predict the potential affinity of an orvinol analog toward the NOP receptor, but the affinity to the NOP receptor is always lower than that of the MOR, which is consistently observed for all of the above orvinols and structure-related analogs identified as either opioids with additional NOP affinity or bifunctional MOR/NOP modulators.…”
Section: Discussionmentioning
confidence: 99%
“…Although a potent antinociceptive effect was observed for abdominal contortions induced by acetic acid, and in both phases of the formalin test, RMD86 only managed to reduce the nociceptive response time during the first 30 min of testing. In comparison, Wen et al, (2011) [ 54 ] analyzing another thiophene derivative, found that the compound increased latency time to 2 h in the hot plate test, being even more effective than morphine which presented antinociceptive effect for approximately 1 h. Then, using pharmacological analysis, it was found that the thiophene derivative presented signs of mechanisms involving opioid receptors.…”
Section: Discussionmentioning
confidence: 99%